2009
DOI: 10.1152/ajplung.00026.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of multidrug resistance-associated protein 1 in the pathogenesis of allergic airway inflammation

Abstract: of multidrug resistance-associated protein 1 in the pathogenesis of allergic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Studies in Abcc1 Ϫ/Ϫ mice confirmed that LTC 4 was a physiologically relevant substrate as these animals exhibited decreased inflammatory responses consistent with impaired LTC 4 export (17). It was suggested that MRP1 inhibitors might be developed that could be useful in the treatment of inflammatory disorders, including those involving the airways such as asthma and chronic obstructive pulmonary disease (17,23). Unfortunately, this has not turned out to be the case.…”
Section: Lipid-derived Signaling Molecules As Substrates Of Mrp1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Abcc1 Ϫ/Ϫ mice confirmed that LTC 4 was a physiologically relevant substrate as these animals exhibited decreased inflammatory responses consistent with impaired LTC 4 export (17). It was suggested that MRP1 inhibitors might be developed that could be useful in the treatment of inflammatory disorders, including those involving the airways such as asthma and chronic obstructive pulmonary disease (17,23). Unfortunately, this has not turned out to be the case.…”
Section: Lipid-derived Signaling Molecules As Substrates Of Mrp1mentioning
confidence: 99%
“…Thus, MRP1 may play a part in inflammatory and other immunological diseases, age-related macular degeneration, cardiovascular disease, and certain neurological disorders as well as tumor progression (4,(22)(23)(24)(25)(26)(27)(28). This potentially broader role of MRP1 in human health and disease has occurred in conjunction with a growing appreciation of its ability to mediate the efflux of bioactive OAs and regulating oxidative stress (25, 29 -31).…”
mentioning
confidence: 99%
“…Although Mrp1 2/2 mice have normal fertility and viability, their ability to transport key endo-and xenobiotics is compromised. Thus, Mrp1 2/2 mice are hypersensitive to the anticancer drug etoposide and exhibit reduced inflammatory responses attributed to disrupted leukotriene homeostasis caused by the inability to efflux leukotriene C4 (Wijnholds et al, 1997;Yoshioka et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It also transports GSH in both its antioxidant and prooxidant (glutathione disulfide) states. Physiologic roles for MRP1 have been established, not only by its ability to modulate GSH homeostasis (Ballatori et al, 2009;Cole, 2013) but also by the characterization of Abcc1 2/2 mice which exhibit impaired inflammatory responses attributed to disrupted leukotriene homeostasis (Wijnholds et al, 1997;Yoshioka et al, 2009). Single-nucleotide polymorphisms (SNPs) are common in genes encoding proteins involved in drug metabolism and transport, and interindividual differences can contribute to differences in absorption, distribution, and elimination that ultimately affect drug efficacy and toxicity (Kroetz et al, 2010;Ieiri, 2012).…”
Section: Introductionmentioning
confidence: 99%